Beyond exegesis: dogmatic reconstruction of special criminal Law - Bracho-Fuenmayor, Pedro Luis (2025)
The research examines the special part of criminal law, which must be understood as the area within which the legal system defines prohibited and mandated conduct ex ante and assigns its punitive consequences. At the same time, it reveals the inherent risks of interpretation replacing legislative determination in cases where the participation of normative elements, references, or open formulas is evident. In this sense, its purpose is to convert the judgment of criminality and its projection towards punishment into reasoning that can be controlled intersubjectively through the construction of a reconstructive sequence. To this end, a legal-dogmatic, systematic-analytical approach of a normative-interpretative nature was adopted, and the analysis was organized through steps that delimit the typical core, distinguishing descriptive and normative components, setting standards of assessment, and excluding analogy to the detriment. It is concluded that a rigorous understanding of the special part of criminal law implies the combination of interpretative limits and principles such as legality, specificity, and lex stricta, as a coherent penal closure since the penalty is derived from verifiable reconstruction and not from argumentative juxtapositions.